Genetic improvement programme in Gir cattle for enhancing milk productivity - SINGH, UMESH; RAJA, T V; ALYETHODI, R R; GAJBHIYE, P U; PRAKASH, B; BHASIN, V (The Indian Journal of Animal Sciences, 2018)
The All India Co-ordinated Research Project (AICRP) on Cattle is implemented in the home tract of Gir cattle for their conservation, propagation and genetic improvement. The involvement of Gir animal owners under the programme has helped to create awareness among the farmers on the importance of this valuable breed. The production of frozen semen doses of genetically superior young bulls and the availability of AI facility at the doorsteps of the farmer has increased the conception rate to a large extent. All lactation production performance of Gir animals maintained in the GP unit revealed better performance than the first lactation production traits. The overall total lactation milk yield, 305-days yield, lactation length, peak yield and dry period were estimated as 3801.0 kg, 2868.30 kg, 457.2 days, 14.80 kg and 68.50 days, respectively. The mean all lactation service period and calving interval were 216.50 and 498.50 days, respectively. The production and reproduction performance of Gir cattle has improved over the years due to the implementation of the project and continuous efforts will be made to propagate this valuable germplasm to the needy people of the country.